Industrial revolution 4.0: Universiti Malaysia Sabah perspective - D Kamarudin D Mudin; How, Siew Eng; Md Mizanur Rahman; Pungut Ibrahim; Marcus Jopony (2018)
Industrial Revolution 4.0 or IR 4.0 is getting the attention of Higher Learning Institutions throughout the world. In the case of Universiti Malaysia Sabah (UMS), “transformation towards University/Industry 4.0” has been identified as one of the nine key result areas (KRAs) in the Strategic Plan 2018-2020. The transformation framework focusses on three areas namely Teaching and Learning 4.0, Smart Eco-UMS 4.0 and Research 4.0. Various initiatives have been planned for each area, some of which are currently being implemented. Previously, under the Strategic Plan 2013-2017, UMS gave great attention on developing and promoting UMS as an eco-campus in line with UMS aspiration to be the reference of eco-campus or green campus in the region. This will be further enhanced under Smart EcoUMS 4.0 in line with the United Nation sustainable development goals. One of the related initiatives is Smart Energy. Through the initiatives under the UMS Ecocampus Plan 2013-2017, a total reduction of 44.50 % in energy consumption was recorded between 2014-2017 compared to 2013 and with 29 % reduction in carbon footprint from 2014-2017. The commitment towards an ecocampus has significant impacts on lowering energy usage and reducing carbon footprint. We believe that the smart energy initiative will further contribute to another level of energy saving and carbon footprint reduction towards reducing the impacts of climate change.